Cloning, characterization and analysis of cat and ben genes from the phenol degrading halophilic bacterium Halomonas organivorans. - Maria de Lourdes Moreno (Public Library of Science (PLoS), 2011)
Background Extensive use of phenolic compounds in industry has resulted in the generation of saline wastewaters that produce significant environmental contamination; however, little information is available on the degradation of phenolic compounds in saline conditions. Halomonas organivorans G-16.1 (CECT 5995(T)) is a moderately halophilic bacterium that we isolated in a previous work from saline environments of South Spain by enrichment for growth in different pollutants, including phenolic compounds. PCR amplification with degenerate primers revealed the presence of genes encoding ring-cleaving enzymes of the β-ketoadipate pathway for aromatic catabolism in H. organivorans. Findings The gene cluster catRBCA, involved in catechol degradation, was isolated from H. organivorans. The genes catA, catB, catC and the divergently transcribed catR code for catechol 1,2-dioxygenase (1,2-CTD), cis,cis-muconate cycloisomerase, muconolactone delta-isomerase and a LysR-type transcriptional regulator, respectively. The benzoate catabolic genes (benA and benB) are located flanking the cat genes. The expression of cat and ben genes by phenol and benzoic acid was shown by RT-PCR analysis. The induction of catA gene by phenol and benzoic acid was also probed by the measurement of 1,2-CTD activity in H. organivorans growth in presence of these inducers. 16S rRNA and catA gene-based phylogenies were established among different degrading bacteria showing no phylogenetic correlation between both genes. Conclusions/significance In this work, we isolated and determined the sequence of a gene cluster from a moderately halophilic bacterium encoding ortho-pathway genes involved in the catabolic metabolism of phenol and analyzed the gene organization, constituting the first report characterizing catabolic genes involved in the degradation of phenol in moderate halophiles, providing an ideal model system to investigate the potential use of this group of extremophiles in the decontamination of saline environments.